Pengaruh kepemimpinan dan motivasi kerja terhadap kinerja karyawan bagian funding dan lending Bank Bukopin Pekanbaru - Putri, Dini Yolanda; Hendriani, Susi; ', Nuryanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research aims to analyze the influence of leadership and motivation to work both simultaneously and partially on employee performance funding and lending Bukopin Bank Pekanbaru. This study used 103 samples and methods of analysis used is a way to test variables, regression testing, and last hypothesis test by simultan and parsial. From the results of the testing that has been done, through the test variable indicates that the variable is a variable that work motivation strong influence on employee performance of the funding and lending Bukopin Bank Pekanbaru. The results of the simultaneous regression (F test) showed that all the independent variables studied had a significant effect on the dependent variable Employee Performance. Partial test (t test) also suggests that work motivation variables have the most significant influence on employee performance variables. The magnitude of the effect that (R2) by the two independent variables (Leadership and work motivation) is jointly affect the dependent variable (employee performance) amounted to 48.6% and the remaining 51.4% can be explained by other factors not examined in this study.Keywords: Leadership, Work Motivation and Employee Performance